Total phenolics content and antioxidant activity of hot water extracts from dried Ficus deltoidea leaves - Said, Wahid; Tengku Muda Mohamed, Mahmud; Mahmood, Maziah; Muda, Ab. Rahim (Malaysian Agricultural Research and Development Institute (MARDI), 2010)
Total phenolics content and antioxidant activity of hot water extracts at temperatures ranging from 55 °C to 107 °C and several sample-to-water ratios (ranging from 1:45 to 1:120, g:ml) were determined for the dried leaves of two accessions of Ficus deltoidea. Total phenolics content and antioxidant activity had higher values in accession MFD 6. A significant difference (p <0.05) in the total phenolics content between the ratios of 1:45 and 1:120 was observed in both accessions at all temperatures tested. However only the temperature of 107 °C caused a significant difference (p <0.01) in antioxidant activity between the ratios of 1:45 and 1:120 in both accessions. A positive linear correlation (R2 = 0.65–0.76) which was statistically significant (p <0.01) was demonstrated between radical scavenging activity and total phenolics content in both accessions. The data indicate that F. deltoidea leaf has potential as a good source of phenolic antioxidants.